Application of Appropriate Technology for Clean Water - Restu Auliani; Riyanto Suprawihadi; Buschhaus Avinash (Yayasan Adra Karima Hubbi, 2023)
Background. The thesis focuses on community service (PkM) conducted by the Ministry of Health Poltekkes institutionally, specifically in the village of Kota Lama II, Secanggang District, Langkat Regency. The study addresses the inadequate access to clean water and poor sanitation conditions in Mr. Mujadi's house, which is among the families included in the PKH (Program Keluarga Harapan) - a conditional cash transfer program in Indonesia. Purpose. The purpose of this community service project is to improve the living conditions of Mr. Mujadi's household by addressing their water and sanitation issues. The project aims to apply science, technology, and art (IPTEKS) through a direct scientific approach to provide sustainable access to clean water and improve sanitation facilities. Method. The objective of this qualitative research is to explore and understand the application of appropriate technology for clean water supply in Kota Lama II Village, Secanggang District, Langkat Regency. The study aims to gain in-depth insights into the experiences, perceptions, and challenges related to the use of appropriate technology for clean water. Results. The results obtained at the end of community service activities in Kota Lama Village II, Secanggang District, Langkat Regency, were built 1 unit of Infiltration galleries. The implementation stages include the initial survey, making Infiltration galleries, compiling filter media, and socializing about clean water and operations and maintenance of Infiltration galleries. Conclusion. Well, water filtered from wells using Infiltration galleries looks clearer and cleaner, odorless and tasteless. This has met the requirements for clean water physically and has met the sanitation aspect.